Gene Expression Modulation by Ayurvedic Rasayanas: A Transcriptomic Study - Dr. Dhaval Kumar Kamaliya; Prof. (Dr.) Sreekanth V. M.; Dr. Tejaskumar Vyas (The Bioscan, 2026)
The Ayurvedic Rasayana are historically known to have rejuvenative and adaptogenic effects but the molecular mechanisms behind the Ayurvedic Rasayana are not well studied. The paper examines the mechanism of Rasayana formulations in controlling gene expression through the transcriptomic method combined with Ayurgenomic concepts. RNA sequencing was applied on the peripheral blood mononuclear cells and the cell models of interest to determine the differentially expressed genes after Rasayana intervention. The results indicate that Rasayanas mediate the important biological pathways, such as oxidative stress response, immune signaling, apoptosis, and metabolic homeostasis, which represent their multi-target therapeutic potential. It is important to note that differences in gene expression patterns were found in different types of Prakriti, which implies the individual response in line with the Ayurvedic theory. Network and pathway analysis also showed that there was a coordinated action of cytokine signaling and mitochondrial functioning. This integrative model brings into focus the intersection of classical knowledge and contemporary omics technologies, which offers new knowledge on the systems-level processes of Rasayanas and justifies their possible involvement in precision and preventive medicine.